GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) PROFILING AND ANTIBACTERIAL ACTIVITY OF SECONDARY METABOLITES PRODUCED BY Bacillus sp. SA11 FROM MANGROVE SOIL - Ni Kadek Widya Diari Ningsih; Anak Agung Gede Indraningrat; Anak Agung Ayu Lila Paramasatiari; Daegeun Choe (Meditory : The Journal of Medical Laboratory, 2025)
Background: Bacterial infections are a major global health concern, including in Indonesia.  This has led to an increased effort to find new antibacterial compounds in natural resources. Bacillus sp. SA11, with reported antibacterial potential, was previously isolated from mangrove soil in Denpasar, Bali. This study further investigated its antibacterial activity.Methods: Secondary metabolites were extracted from Bacillus sp. SA11 liquid culture using ethyl acetate. The extract was then screened for antibacterial activity against Escherichia coli ATCC 25922, Streptococcus mutans FNCC 0405, Staphylococcus aureus ATCC 25923, and Klebsiella pneumoniae ATCC 70060 using the Kirby-Bauer method (three replicates). The chemical composition of the extract was analysed via GC-MS.Results: The ethyl acetate extract showed inhibition zones for E. coli, S. mutans, S. aureus, and K. pneumoniae of 11.7 ± 1.11 mm, 10.22 ± 1.5 mm, 8.7 ± 0.94 mm, and 7.2 ± 0.67 mm, respectively. GC/MS analysis identified 165 compounds, 20 of them have been  previously linked to antibacterial activities. The five most abundant compounds are n-hexadecanoic acid (6.91%), 2-butoxyethyl acetate (6.3%), Bis(2-ethylhexyl) phthalate (4.45%), Phthalic acid, di(2-propylpentyl) ester (4.45%) and Benzene, 1,3,5-trimethyl- (Mesitylene).Conclusion: These findings provide preliminary evidence that Bacillus sp. SA11, isolated from the mangrove ecosystem, has the potential to produce antibacterial compounds.